LEGAL PROTECTION OF DISPUTED LAND DEED OFFICIALS IN THE BANKRUPTCY ESTATE BY THE CURATOR IN RELATION TO THE PRINCIPLE OF JUSTICE - Amini, Nyak; Yusdiansyah, Prof. Dr. Efik; Rivandi, Dr. Dhody Ananta (YURIS: Journal of Court and Justice, 2024)
Bankruptcy occurs when a person or entity stops paying its overdue debts, leading to the management of their assets by a curator. The curator oversees and manages the bankruptcy estate. The problem of bankruptcy estate often arises due to the transfer deed issued by the Land Deed Official (PPAT) which is considered incorrect by the curator, resulting in the Land Deed Official being sued and creates uncertainty as well as injustice for the Land Deed Official. This research will examine how the land law system regulates land sale and purchase transactions in the agrarian field in Indonesia, which was previously regulated in Government Regulation No. 24 of 1997 concerning Land Registration by applying a negative publication system with positive elements. This research applies empirical juridical research methods. The findings of this research identified that the legal system of land sales and purchases in Indonesia can lead to disputes in bankruptcy estates managed by curators, particularly concerning the principle of prudence. The Land Deed Official is responsible for errors or violations in the deeds they create but not for inaccuracies provided by the parties involved. If the parties provide false information, the responsibility lies with them, rather than with the Land Deed Official who only records the submitted information.